2021
DOI: 10.1186/s12936-021-03601-9
|View full text |Cite
|
Sign up to set email alerts
|

Usage of and satisfaction with Integrated Community Case Management care in western Uganda: a cross-sectional survey

James S. Miller,
Palka Patel,
Sara Mian-McCarthy
et al.

Abstract: Background In some areas of Uganda, village health workers (VHW) deliver Integrated Community Case Management (iCCM) care, providing initial assessment of children under 5 years of age as well as protocol-based treatment of malaria, pneumonia, and diarrhoea for eligible patients. Little is known about community perspectives on or satisfaction with iCCM care. This study examines usage of and satisfaction with iCCM care as well as potential associations between these outcomes and time required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
2
1
Order By: Relevance
“…Timely services were statistically significantly associated with Uptake of ICCM services in Apac district (P<0.00, AOR 12.7(3.4-47), caregivers who received timely services were 12 times more likely to accept ICCM services by the VHT than those who did not receive timely services. These results are similar to those revealed by Miller and colleagues in which timely access to services offered by VHTs increased the acceptability of ICCM services (J. S. Miller et al, 2021;Mukanga et al, 2012). In the circumstances of a sick child, there is always anxiety among any caregiver and hence if care is rendered in a timely way, this builds confidence in the service offered hence acceptability is likely to be high.…”
Section: Factors Associated With Uptake Of Iccm Services Among Caregi...supporting
confidence: 89%
“…Timely services were statistically significantly associated with Uptake of ICCM services in Apac district (P<0.00, AOR 12.7(3.4-47), caregivers who received timely services were 12 times more likely to accept ICCM services by the VHT than those who did not receive timely services. These results are similar to those revealed by Miller and colleagues in which timely access to services offered by VHTs increased the acceptability of ICCM services (J. S. Miller et al, 2021;Mukanga et al, 2012). In the circumstances of a sick child, there is always anxiety among any caregiver and hence if care is rendered in a timely way, this builds confidence in the service offered hence acceptability is likely to be high.…”
Section: Factors Associated With Uptake Of Iccm Services Among Caregi...supporting
confidence: 89%
“…While HSR measurement is not widely reported in the literature for CHW-delivered care, our findings for these patient-reported experiences are similar but slightly lower than the results from Miller and colleagues who conducted a cross-sectional study in Uganda among individuals receiving iCCM from village health workers (VHWs) [ 21 ]. Using a five-point Likert scale, they found that 60% rated their overall experience as very good/excellent, and 92% stated that they were confident/very confident in the VHW’s overall abilities.…”
Section: Discussioncontrasting
confidence: 49%
“…While patients’ families were not directly involved in developing the research question or outcome measures for this study, community members play a key role in selecting the VHWs who provide care in their communities. In a separate study, we have also sought to understand families’ experience of and satisfaction with iCCM care to identify programme strengths and areas for improvement 25. Evaluation of iCCM quality of care has also helped tailor the content of VHW refresher trainings and other quality improvement efforts.…”
Section: Methodsmentioning
confidence: 99%